Working experiences of Iranian retired nurses: A content analysis study. Issue 5 (29th May 2013) - Nobahar, Monir; Ahmadi, Fazlollah; Alhani, Fatemah; Fallahi Khoshknab, Masood
<x xml:space="preserve">Abstract</x> Understanding the experiences of retired nurses can be useful in increasing self‐confidence, motivation to work and work enthusiasm among nurses. The purpose of this study was to explore the work experiences of Iranian retired nurses. A qualitative design was conducted using a content analysis approach. Purposive sampling was used to choose the study participants. Semi‐structured interviews were held to collect the perspectives of 20 retired nurses (10 female and 10 male). Two main themes emerged in the data analysis: 'work problems and unpleasant experiences in a sense' with subthemes 'exhausting work', 'insufficient salary', 'inappropriate relation' and 'unsuitable social position'; and 'job satisfaction and pleasant experiences in a sense' with subthemes 'divine satisfaction and religious belief', 'satisfaction of patients and their companions' and 'love of nursing profession and relaxation experience'. The findings indicate the challenges that nurses face after retirement. These experiences will help nurse managers to adopt appropriate measures to support nurses after retirement.